Kegiatan Pengukuran Antropometri Pada Populasi Lanjut Usia Sebagai Deteksi Dini Obesitas Dan Komplikasi Terkait Obesitas - Robert Kosasih; Naufal Rayhan; Brian Albert Gaofman; Joshua Kurniawan; Fernando Nathaniel; Alexander Halim Santosa (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
Obesity, characterized by excessive accumulation of body fat, increases susceptibility to chronic disease and adversely impacts overall quality of life. Elderly people often exhibit higher fat mass and lower muscle mass and bone density, influenced by reduced physical activity, hormonal changes, and metabolic adjustments. Visceral fat accumulation is of particular concern because of its association with metabolic syndrome, insulin resistance, diabetes, hypertension, and cardiovascular disease. This activity uses the PDCA (Plan-Do-Check-Act) framework to screen for obesity in the elderly using Body Mass Index (BMI) and waist circumference measurements. Activities were held at St. Fransiskus Assisi, Jakarta involving 36 participants. The study revealed that 16 participants (44.5%) and 30 people (83.3%) were obese and centrally obese, respectively. Early detection and intervention through anthropometric measurements are very important in managing health risks related to obesity in the elderly, so as to improve their quality of life and reduce morbidity and mortality.